Examining the Support for Victims of Sexual Violence in Campus: A SWOT Analysis of Permendikbudristek Number 30 of 2021 - Haironi Ayu Wulandari; Amy Yayuk Sri Rahayu (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2023)
The controversy surrounding Minister of Education, Culture, Research, and Technology Regulation (Indonesian abbreviation: Permendikbudristek) No. 30 of 2021 on the Prevention and Handling of Sexual Violence (PHSV) in campus environment has become a heated topic of discussion at present. When the PHSV regulation was issued, some religious figures interpreted the phrase “without the victim’s consent” in Article 5 as having multiple meanings. This particular phrase sparked controversy among the public and religious figures who argued that it could be perceived as the government legalizing promiscuous behavior. Consequently, it divided people into two groups: those in favor of the PHSV regulation and those against it. To gauge public response to the PHSV regulation, this study was conducted as a benchmark for evaluating its implementation. The study employed SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) as a reference for data collection and examination. SWOT analysis considers both internal factors and external factors to determine the weight of each factor, leading to conclusions regarding the issues at hand. Based on the conducted analysis, the PHSV regulation received a positive response from the public, with people expressing their support for the regulation. The PHSV regulation possesses strengths and opportunities that make it feasible as an instrument to minimize instances of sexual violence occurring within campus environments.